Plus pluris mittere debet: philological notes on Nebrija’s Introductiones Latinae edited by his pupil Cristóbal Escobar - Reyes Montero , Juan Francisco (Cuadernos de Filología Clásica. Estudios Latinos, 2024)
It is known from previous studies that the humanist Cristóbal Escobar, Andalusian by birth and Sicilian by adoption, used more than one edition to prepare his own edition of the Antonio de Nebrija’s Introductiones Latinae, his master, intended for the Italian public and published in Venice in 1512. This work identifies, on the basis of the collation and analysis of variants, which editions were used by the Nebrija’s disciple. The results of the study have also made it possible to determine which edition was used for which content.